PENGARUH LINGKUNGAN KELUARGA TERHADAP MOTIVASI BELAJAR SISWA - Muhasiye, Muhasiye; Genjik, Bambang; Syahrudin, Husni (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstract This thesis entitled, "The Influence of Family Against Student Motivation in Economy Class XI Lesson in SMA Muhammadiyah 2 Pontianak". Variables in this study consist of independent variable (X), namely Family Environment and dependent variable (Y), that is Learning Motivation. The method used in this research is quantitative descriptive method with the form of research. Population in this research is all student of class XI Ips Sma Muhammadiyah 2 Pontianak. Where the sample in this research is the students of class XI Ips I Sma Muhammadiyah 2 Pontianak produced by cluster random sampling technique. The results showed that the family environment has an influence on the motivation of students in the class XI Sma Muhammadiyah 2 Pontianak with the formulation Y = 5.676 + 0.657X. Based on the calculation using SPSS program, t counters 4.506, while t table with respondents 37 students who have degrees of freedom df = n - k or 37-2 = 35, then t table is 2.030, from the results, compare between t arithmetic with t table. Resulted t count> t table (4.506> 2.030) and with magnitude of ixuhan 0,606 which means positive influence. Social Influence Against Student Motivation in Economy Class XI at Sma Muhammadiyah 2 Pontianak. Keywords: Family Environment, Motivation on Learn